Zur Entwicklung des Anspruchslohns in Deutschland - Alfred Boss (Kiel Institute for the World Economy (IfW), 2008)
Due to labor market reforms in Germany some years ago, the incentives to work changed. The paper analyzes the effects on the reservation wages for specific groups. It is assumed that reservation wages are determined by the replacement rates implied by the system of unemployment benefits and by the rules of means-tested social assistance. In addition, the paper describes the development of the replacement rates in the recent decades. As a side effect, it is intended to support the search for an indicator for the reservation wage which can be used to explain the unemployment rate in a macroeconomic model for Germany. It turns out that the replacement rates increased in the period 1950 to 1975. Thereafter, the rates for the specific groups developed differently. However, in 2008 the rates are higher than they had been in the fifties and the sixties.
Keywords: H24; 330; Unemployment benefits; net wages; reservation wages; incentives to work; Anspruchslohn; Arbeitslosenversicherung; Arbeitsangebot; Ökonomischer Anreiz; Deutschland